Analisis Pengelolaan Pakan Kambing Peternak Rakyat di Desa Sindang Agung, Kecamatan Tanjung Raja, Kabupaten Lampung Utara. - R Anggraeni; R Noviadi; Y Sukaryana (PETERPAN (Jurnal Peternakan Terapan), 2020)
This study aims to analyze the management of goat feed carried out in Sindang Agung Village, Tanjung Raja District, North Lampung Regency. This research was conducted for 2 months in Sindang Agung Village through a survey method with qualitative field analysis. research shows that the management of goat tenak feed carried out in Sindang Agung Village is still done traditionally, where goats are only kept in pens and feed is carried out by the breeders continuously. Feeding goats that only relies on the available forage in the form of field grass, leaves on plantation land and on the side of the road in Sindang Agung Village. Farmers in Sindang Agung Village do not provide additional feed such as concentrate or other additional feed, Feeding goats is carried out in the morning and evening by means of cut and carry.